Islamic finance: Meeting Global Aspirations and Growth Potential - UK Model - salih hasan, mohammed; Hussein ali, Nassr; Omer abdulwahid abbas; jumaah alwan , mohammed (Journal of Excellence for Economics and Management Research, 2022)
The purpose of this research is to describe the Islamic financial market and products, with particular emphasis on the growth of Islamic finance in the UK market. The analytical descriptive approach has been used because it will help to collect quantitative and qualitative data to answer the research question or test the research hypothesis. The results indicate that Islamic and traditional banks with the Islamic window promote investment in the UK through the financing of real estate, insurance services and financing of transport projects without interest charges on loans. (FSA) Encourage the Government to develop Islamic banking, develop market and demand, and develop Islamic finance products and services that contribute to the growth of Islamic banking services in the United Kingdom.